Reactor Dosimetry: 16th International Symposium 2018
DOI: 10.1520/stp160820170090
|View full text |Cite
|
Sign up to set email alerts
|

Design of Separated Element Reflector Experiments in CROCUS: PETALE

Abstract: The present article describes the preliminary design studies for PETALE (Programme d’Etude en Transmission de l’Acier Lourd et ses Eléments), an oncoming experimental program in the CROCUS reactor. Within the framework of the Venus-Eole-Proteus collaboration, PETALE continues the nuclear data validation efforts required for modeling GEN-III pressurized water reactors with heavy steel reflectors. The inelastic scattering cross sections at around 1 MeV of iron-56, as well as nickel and chromium isotopes, will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…A zoom on the interface between CROCUS and the metal reflector shows the first foil with a width multiplied by 10 in order to be visible (1 g of indium for the first foil instead of 0.1 g). A first parametric study [2] performed with the MCNP code [10] has shown that the dimension of the plates can be limited to 30 × 30 cm 2 with acceptable border effects. In order to obtain precise data for the different isotopes composing a heavy reflector, the measurements will be repeated for different plate compositions: Fe, Ni, Cr, and steel.…”
Section: Description Of the Petale Experimental Programmementioning
confidence: 99%
See 1 more Smart Citation
“…A zoom on the interface between CROCUS and the metal reflector shows the first foil with a width multiplied by 10 in order to be visible (1 g of indium for the first foil instead of 0.1 g). A first parametric study [2] performed with the MCNP code [10] has shown that the dimension of the plates can be limited to 30 × 30 cm 2 with acceptable border effects. In order to obtain precise data for the different isotopes composing a heavy reflector, the measurements will be repeated for different plate compositions: Fe, Ni, Cr, and steel.…”
Section: Description Of the Petale Experimental Programmementioning
confidence: 99%
“…Such experiments can be employed to validate the present nuclear data libraries and numerical codes, or can be used to improve the nuclear data libraries via assimilation techniques. In this frame, the present work is related to the PETALE experimental programme [1,2] during its design phase. This programme aims at providing better constraints on the neutron cross sections in heavy reflectors for water reactors such as the European Pressurized Reactor (EPR) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…CROCUS is an experimental zero-power reactor, uranium-fuelled and water-moderated, dedicated to education in radiation and reactor physics, and to research [6][7][8][9][10][11][12][13][14][15][16][17]. A complete description of the core can be found in the International Reactor Physics Experiments Handbook (IRPhE) [18].…”
Section: The Crocus Reactormentioning
confidence: 99%
“…HE CROCUS reactor is a two-zone, uranium-fuelled light water moderated facility operated by the Laboratory for Reactor Physics and Systems Behaviour (LRS) at the Swiss Federal Institute of Technology Lausanne (EPFL). With a maximum power of 100 W, it is a zero-power reactor used for teaching and research purposes, most recently for studies on intrinsic and induced neutron noise, highly-localized measurements, and nuclear data [1]- [19]. Knowledge of the reactor power is a mandatory quantity for a safe operation.…”
Section: Introductionmentioning
confidence: 99%